2013
DOI: 10.3390/d5040750
|View full text |Cite
|
Sign up to set email alerts
|

Novel Endophytic Trichoderma spp. Isolated from Healthy Coffea arabica Roots are Capable of Controlling Coffee Tracheomycosis

Abstract: Abstract:One of the biggest threats to coffee growers in East Africa are emerging vascular wilt diseases (tracheomycosis) caused by Fusarium spp. Many Trichoderma species are known to be natural antagonists of these pathogens and are widely used in biological control of fungal plant diseases. More recently, several Trichoderma spp., which exhibited high antifungal activity have been isolated as endophytes. Consequently, we have investigated the presence and the antagonistic activity of endophytic Trichoderma i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 52 publications
1
21
0
1
Order By: Relevance
“…The latter contradicts studies targeting Coffea arabica, for which Trichoderma was shown to inhabit its rhizosphere but was not recovered as a leaf endophyte (Mulaw et al, 2010;Vega et al, 2010;Mulaw et al, 2013). However, these other studies were conducted in different geographic regions and following different protocols.…”
Section: Discussionmentioning
confidence: 82%
“…The latter contradicts studies targeting Coffea arabica, for which Trichoderma was shown to inhabit its rhizosphere but was not recovered as a leaf endophyte (Mulaw et al, 2010;Vega et al, 2010;Mulaw et al, 2013). However, these other studies were conducted in different geographic regions and following different protocols.…”
Section: Discussionmentioning
confidence: 82%
“…yang diisolasi dari akar Coffee arabica yang mampu mengendalikan tracheomycosis pada kopi (Mulaw et al, 2013) Hasil analisis sekuens ITS DNA berdasarkan database pada program BLAST-N menunjukkan, bahwa isolat Swn-1, isolat Swn-2 dan isolat Psr-1 mempunyai hubungan kekerabatan dengan Trichoderma harzianum, isolat Ksn dengan Trichoderma asperellum, isolat Psr-2 dengan Trichoderma gamsii dan isolat Psr-3 dengan Trichoderma koningiopsis, dengan tingkat kemiripan 99 % (Tabel 2).…”
Section: Hasil Dan Pembahasanunclassified
“…17 Diverse Trichoderma species were also found among coffee endophytic fungi that colonize healthy tissues. 18,19 Trichoderma population was enriched in coffee waste containing caffeine »0.1% in wet weight. 20,21 These observation suggest a specific relationship between caffeine and Trichoderma.…”
Section: Introductionmentioning
confidence: 99%